Analysis of STARS as a Sustainability Assessment System Universally Usable in Higher Education - Maragakis, Antonios; van den Dobbelsteen, Andy (A+BE | Architecture and the Built Environment, 2018)
Sustainability assessment has become an important tool for measurement of higher education institutions. Although there are many potential tools for measuring an institutions level of sustainability, this paper explores the use of STARS as a system for higher education sustainability that could be used universally by all higher education institutions, as well as enables comparison between institutions. The results of this paper address the effectiveness of STARS to fulfill this need, as well as the further development needed in order to fully encompass sustainability and stakeholder needs.